EFEKTIFITAS ELEVASI DAN PRODUK TERBAIK ESTIMASI CURAH HUJAN RADAR CUACA BERDASARKAN KLASIFIKASI AWAN - Widomurti, Laksita; Suswantoro, Denni Kartono (Pusdiklat BMKG, 2020)
Weather radar is one of the remote sensing techniques that is used to provide weather information so that it has a very important role to facilitate services and information. In addition, another benefit of weather radar is that it can estimate rainfall so it is important to know the effectiveness of the Bima weather radar and the best radar product for estimating rainfall based on rain cloud classification. The method used in this research is descriptive analytic and statistically processed. Separation of cloud types by combining two methods, namely the rainfall limit value of 10 mm / hour and 38 dBZ, for clouds with rainfall ≥ 10 mm / hour and the reflectivity value ≥ 38 dBZ are categorized as convective clouds while for values <10mm / hour and < 38 dBZ is categorized as a stratiform cloud.Thera are three methods to determine the best product of weather radar,namely Mean Error (ME), Mean Absolute Error (MAE) and Probability of Detection (PoD). The results of this study shown that the Bima weather radar is effective for coverage the entire scanning area at an elevation of 11.7 °, so to get maximum coverage result of observation area. But not effective to knowing the cloud structure that only detected by radar on loest elevation 0.5 0. For the best product of Bima weather radar to estimating rainfall based on cloud classification with error value consideration is Surface Rainfall Intensity (SRI)